2020
DOI: 10.1063/5.0018037
|View full text |Cite
|
Sign up to set email alerts
|

Lactones formation during monosaccharide's caramelization in ethanolic-aqueous solutions

Abstract: Caramelized carbohydrate's products contain ester functions, which are play a significant role in foodstuff properties, but their formation processes are not considered in detail [1]. In present work sugar lactone's fragments in monosaccharide's thermodestruction products structure were identified using FTIR spectroscopy, several characteristic bands were choosing for structural analysis. The bands at 1164 and 1255 cm -1 are symmetric and asymmetric stretching vibrations of the -C(=O)-O-C-group respectively. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Over several decades, caramels have been used in the food industry as a colorant (Chazelas et al ., 2020; Cherepanov & Botalova, 2020). Cookies, bread, ice cream cones and muffins can be given as some examples of caramel‐containing products (Sengar & Sharma, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over several decades, caramels have been used in the food industry as a colorant (Chazelas et al ., 2020; Cherepanov & Botalova, 2020). Cookies, bread, ice cream cones and muffins can be given as some examples of caramel‐containing products (Sengar & Sharma, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon can be expected in roasted oils. Among the detected esters, lactones can be formed from phenolic acids, carbohydrates, and carotenoids [ 27 , 33 ]. Two parallel reactions such as the enolate Spengler-Pfannenstiel degradation and the Cannizzaro reaction of α-dicarbonyl compounds can lead to various saccharic acids, which may form lactones [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the detected esters, lactones can be formed from phenolic acids, carbohydrates, and carotenoids [ 27 , 33 ]. Two parallel reactions such as the enolate Spengler-Pfannenstiel degradation and the Cannizzaro reaction of α-dicarbonyl compounds can lead to various saccharic acids, which may form lactones [ 33 ]. In this study, the reduction in both polyphenolic compounds and carotenoids was observed at the highest roasting temperature, which can be a possible source of lactones.…”
Section: Discussionmentioning
confidence: 99%